Clinical Case Report of Expansive Laminoplasty for Cervical Myelopathy Due to Both Disc Herniation and Developmental Cervical Spinal Canal Stenosis in Older Adolescents. Issue 8 (February 2016) - Zhou, Hua; Sun, Yu; Zhang, Fengshan; Dang, Gengting; Liu, Zhongjun
Abstract : Abstract: Reports on adolescent patients with cervical myelopathy who underwent anterior cervical discectomy and fusion are scarce. However, to our knowledge, no cases of expansive laminoplasty for cervical myelopathy associated with progressive neurological deficit after a series of conservative treatment, caused by both disc herniation and developmental cervical spinal canal stenosis, have been reported. From January 2006 to July 2012, we retrospectively studied 3 patients in late adolescence presenting with cervical myelopathy who underwent expansive unilateral open-door laminoplasty at our hospital. The outcomes after the surgery were evaluated according to the Japanese Orthopedic Association scores. Symptoms presented by these patients were due to both disc herniation and developmental cervical spinal canal stenosis. No major complications occurred after the surgical procedures. The median follow-up time was 66 months (range 36–112 months). The Japanese Orthopedic Association scores after surgery showed a significant increase. Long-term outcomes after surgery were satisfactory according to the evaluation criteria for the Japanese Orthopedic Association scores. However, the ranges of motion of the cervical spine decreased, especially the ranges of motion on flexion after surgery showed a significant decrease. Expansive laminoplasty is helpful for older adolescent patients with cervical myelopathy due to both disc herniation and developmental cervical spinal canal stenosis, presenting with progressive neurological deficit after long conservative treatment.